Sentidos e significados atribuídos por professores de diferentes áreas à interdisciplinaridade - Machado, Cristiane Silva (2018)
The term Interdisciplinarity has been widely used in the educational context. As I am inserted in this context, I established as objective of this research to analyze the senses and meanings attributed by teachers from different areas of knowledge to Interdisciplinarity, present in the subject Diversity, Inclusion and Working World, included in the Secondary school curriculum by the Education Secretary of Minas Gerais state. The present study is anchored in the concept of Interdisciplinarity, discussed by several authors such as Fazenda (1979, 1995, 2008, 2011a, 2011b, 2011c, 2013a, 2013b), Paviani (2005), Santomé (1989, 1996), Frigotto (1995) and Japiassu (1976). Despite the differences among the scholars whose proposals support this research , it can be stated that they all share a meaning of Interdisciplinarity: they emphasize that it is not a science or a new discipline, but a possibility of dialogue between the different disciplines and their concepts, without neglecting the knowledge produced in each Science. This work is also supported by the concepts of Interdisciplinarity reformulated in documents of the Ministry of Education (MEC), in the National Curricular Parameters for Primary and Secondary Education, in the Law of Guidelines for National Education and in National Curricular References, considering the role they play in basic education. The participants in this research were teachers from three different areas of the public teaching system: Portuguese Language, Mathematics and Biology. Methodologically, the research was characterized as a case study (ANDRÉ, 2008). The data were collected through video recording and analyzed and interpreted based on the linguistic realization of the teachers, focusing on the senses they attributed to Interdisciplinarity. The results show that this concept, though widely discussed in teacher education contexts and present in the official documents that guide education in Brazil, is still fragmented, requiring more investment in teacher education, so that it becomes truly interdisciplinary and, consequently, permeates Brazilian students´ learning process